ANALISIS IMPLEMENTASI SISTEM ADMINISTRASI PERPAJAKAN PADA INSTANSI PEMERINTAH DALAM MENDUKUNG KEPATUHAN PAJAK - Kholifatusholehah; Supriyanto; Nofitasari , Susi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of tax administration systems in government institutions in supporting taxpayer compliance. The research employs a qualitative approach with a descriptive method to provide an in-depth understanding of the phenomenon. Data were collected through observation, documentation, and literature review from relevant academic and official sources. The findings indicate that the implementation of technology-based tax administration systems, such as e-Filing and e-Billing, has significantly improved service efficiency, accessibility, and transparency. These improvements contribute to better supervision and encourage higher levels of taxpayer compliance. However, several challenges remain, including limited human resources, insufficient digital literacy among taxpayers, and suboptimal utilization of available technology. These constraints hinder the effectiveness of the system in achieving optimal compliance outcomes. Therefore, continuous improvements are required, particularly in enhancing human resource capacity, strengthening digital infrastructure, and increasing public awareness through socialization and education programs. Overall, the study highlights that a well-implemented and technology-driven tax administration system plays a crucial role in fostering sustainable taxpayer compliance within government institutions.